A service requirements engineering method for a digital service ecosystem. Issue 2 (June 2016) - Immonen, Anne; Ovaska, Eila; Kalaoja, Jarmo; Pakkala, Daniel
Abstract A digital service ecosystem enables value creation and the co-development of services in a value network under a common ecosystem regulation. The ecosystem members are able to focus on their core competences and can strengthen their forces by co-operating; yet remaining able to act independently. However, due to regulated environment, the ecosystem elements—i.e. ecosystem members, capabilities, infrastructure and the existing ecosystem assets—have an influence on digital service engineering, especially in the service requirements engineering phase. The main contribution of this paper is to describe how to specify the requirements of digital services in a digital service ecosystem. To this aim, this paper introduces the basic definitions and elements of the digital service ecosystem, and a scenario-based service requirement engineering (RE) method for the digital service ecosystem. A practical example is given to illustrate the use of the RE method. The collected feedback from the RE method users highlights the user experiences on the advantages and limitations of the proposed method.